2013
DOI: 10.1016/j.lmot.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The magic number 70 (plus or minus 20): Variables determining performance in the Rodent Odor Span Task

Abstract: The olfactory span task (OST) uses an incrementing non-matching to sample procedure such that the number of stimuli to remember increases during the session. The number of consecutive correct responses (span length) and percent correct as a function of the memory load have been viewed as defining rodent working memory capacity limitations in several studies using the OST. However, the procedural parameters of the OST vary across experiments and their effects are not well understood. For example, in several stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 27 publications
(59 reference statements)
6
55
0
Order By: Relevance
“…This adaptation of the OST procedure allowed for a comparison of performance across trials unbiased by concurrent variation in chance performance. Average baseline performance was similar to earlier studies using the dualcomponent procedure both in terms of span and percent correct accuracy (MacQueen et al 2011;April et al 2013;Galizio et al 2013). Accuracy declined as the number of stimuli to remember increased, demonstrating that two-comparison odor span performance was capacity dependent.…”
Section: Discussionsupporting
confidence: 75%
“…This adaptation of the OST procedure allowed for a comparison of performance across trials unbiased by concurrent variation in chance performance. Average baseline performance was similar to earlier studies using the dualcomponent procedure both in terms of span and percent correct accuracy (MacQueen et al 2011;April et al 2013;Galizio et al 2013). Accuracy declined as the number of stimuli to remember increased, demonstrating that two-comparison odor span performance was capacity dependent.…”
Section: Discussionsupporting
confidence: 75%
“…However, using the OST procedure, April, Bruce and Galizio (2013) found that if the number of distracting stimuli is controlled and held constant throughout the testing session, the number of stimuli that rats can remember does not appear to be limited; indeed, rats showed accurate performance on the task with over 70 odor stimuli to remember. This finding is inconsistent with a limited capacity, working memory account.…”
Section: Introductionmentioning
confidence: 99%
“…April et al (2013) used a probe procedure in which no new stimuli were presented on certain trials to assess the relative importance of recent familiarity with odor stimuli. They found that rats tended to select the odor that had been encountered least recently on such trials, but that number of stimuli visited and latencies to respond were much longer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations